Excreted Trypanosoma brucei proteins inhibit Plasmodium hepatic infection - Adriana Temporão (Public Library of Science (PLoS), 2021)
Malaria, a disease caused by Plasmodium parasites, remains a major threat to public health globally. It is the most common disease in patients with sleeping sickness, another parasitic illness, caused by Trypanosoma brucei. We have previously shown that a T. brucei infection impairs a secondary P. berghei liver infection and decreases malaria severity in mice. However, whether this effect requires an active trypanosome infection remained unknown. Here, we show that Plasmodium liver infection can also be inhibited by the serum of a mouse previously infected by T. brucei and by total protein lysates of this kinetoplastid. Biochemical characterisation showed that the anti-Plasmodium activity of the total T. brucei lysates depends on its protein fraction, but is independent of the abundant variant surface glycoprotein. Finally, we found that the protein(s) responsible for the inhibition of Plasmodium infection is/are present within a fraction of ~350 proteins that are excreted to the bloodstream of the host. We conclude that the defence mechanism developed by trypanosomes against Plasmodium relies on protein excretion. This study opens the door to the identification of novel antiplasmodial intervention strategies. Author summary Malaria and sleeping sickness are parasitic illnesses that overlap geographically, making it likely that co-infections between the two causative parasites occur. It was previously shown that when mice are first infected with Trypanosoma brucei, there was an attenuation of the subsequent infection by Plasmodium. Here we sought to assess whether an active T. brucei infection was required for this impairment, and to unravel the mechanism behind this phenomenon. We found that not only T. brucei total lysates are able to inhibit Plasmodium liver infection, but also that mice that received these lysates are partly protected from developing severe malaria pathology. We further showed that this protective effect is mediated by proteins excreted by trypanosomes. Our study paves the way to the development of novel antiplasmodial intervention strategies, based on the mechanism involved during the co-infection between T. brucei and Plasmodium.